Localization of Sound Sources in Normal Hearing and in Hearing Impaired People - NIEWIAROWICZ, Marek; KACZMAREK, Tomasz (Archives of Acoustics, 2011)
This article presents results of investigations of the angle of directional hearingacuity (ADHA) as a measure of the spatial hearing ability with a special emphasison people with hearing impairments. A modified method proposed by Zakrzewskihas been used – ADHA values have been determined for 8 azimuths in the horizontalplane at the height of the listeners’ head. The two-alternative-forced-choice method(2AFC), based on a new system of listeners’ responses (left – right instead of nodifference – difference in location of sound sources) was the procedure used in theexperiment. Investigations were carried out for two groups of subjects: normal hear-ing people (9 persons) and hearing impaired people (sensorineural hearing loss andtinnitus – 9 persons). In the experiment different acoustic signals were used: sinu-soidal signals (pure tones), 1/3 octave noise, amplitude modulated 1/3 octave noise,CCITT speech and traffic noises and signals corresponding to personal character oftinnitus for individual subjects. The results obtained in the investigations showed,in general, a better localization of the sound source for noise type signals than thosefor tonal signals. Inessential differences exist in ADHA values for particular signalsbetween the two groups of subjects. On the other hand, significant differences fortinnitus signals and traffic noise signals were stated. A new system of listeners’ re-sponses was used and appeared efficient (less dispersion of results compared to thestandard system).